Structural analysis of effector functions related motifs, complement activation and hemagglutinating activities in Lama glama heavy chain antibodies - Saccodossi, Natalia (2012)
Heavy chain antibodies (HCAbs), devoid of the light chains and the CH 1 domain, are present in the serum of camelids. IgG 2 and IgG 3 are HCAbs; whereas IgG 1 has the conventional structure. In order to study the immunological properties of llama HCAbs, from which to date little is known, llamas (Lama glama) HCAbs cDNA were cloned, sequenced and compared with other mammalian Igs. The sequence analysis showed that llama HCAbs cDNA organization is similar to other mammalian Igs and the presence of conserved binding motifs to Protein A, Protein G, FcγRI, FcγRIII and C1q in HCAbs were observed. In a previous work, different IgG isotypes purified by Protein A and Protein G chromatography, were assayed for their ability to fix complement. Both IgG 1 and the total serum were able to fix complement, whereas IgG 2 and IgG 3 fixed complement even in the absence of antigen (anti-complementary activity). Therefore, in this work we performed the complement activating activity of the different IgG isotypes purified under physiological conditions using Sephadex G-150 and their ability to induce hemagglutination. Llamas were immunized with sheep red blood cells (RBC) stroma and the different isotypes were purified from sera. Whole serum and IgG 1 could activate complement; however, HCAbs (IgG 2+IgG 3) could not, despite the presence of the C1q binding motif in their primary sequence. Unlike IgG 1, the fraction corresponding to IgG 2+IgG 3 did not display hemagglutinating activity. Our findings suggest that HCAbs cannot crosslink efficiently with different antigens and that the C1q binding site might be hindered by the proximity of the variable domains. © 2011 Elsevier B.V.